The Effect of Educational Games on the Level of Motivation in Science of Grade IV Students in Angel Villarica Central School - Farrah Jean Calatrava; Kaye Jay Lacsamana; John Rex Revilla; Jovenil Bacatan (Journal of Science and Science Education, 2022)
The concern of this study is to determine The Effect of Educational Games on the Level of Motivation of Grade 4 Students in Angel Villarica Central Elementary School. A quantitative research design employing an experimental method was used in the study. The essential data were gathered from a total number of seventy-three (73) respondents, 36 students from the control group and 37 students from the experimental group, with the aid of a questionnaire validated by a panel of experts. The statistical tools used in this study were Average Weighted Mean and t-test for Independent Sample Means. The study proved that there was no significant difference between the mean gain scores of the experimental and control groups. It means that the use of educational games has no significant effect on the level of motivation in science. However, educational games can be considered as an alternative method in delivering the Science lesson. It was being recommended in the study to conduct a similar study in the future to confirm that educational games have no effect on the level of motivation and involve a wider scope in the conduct of the study